P06 CLIF-C AD score outperforms other prognostic scoring tools in predicting 30-day mortality in patients with acute alcohol-related hepatitis. (20th September 2022) - Gosson, Caroline; Mandour, Omer; Forton, Daniel; Singanayagam, Arjuna
Abstract : Introduction: Severe acute alcohol-related hepatitis (sAAH) is associated with a high short-term mortality. Accurate prognostication is important to guide decision making for corticosteroid use, and to counsel patients and carers. Several models have been used to determine prognoses in this group, such as the Maddrey's discriminant function (MDF) and Glasgow Alcoholic Hepatitis (GAHS) score. However, newer scores used in the acute decompensated cirrhosis and acute-on-chronic liver failure populations (e.g. CLIF-C AD and ALBI scores) have not been tested in an untargeted way on this population. We aimed to compare the MDF, MELD, GAHS, ALBI, NLR and CLIF-C-AD scores as predictors for admission to intensive care, 30- and 90-day mortality in patients admitted with any severity of acute alcohol-related hepatitis. Methods: We retrospectively identified 66 patients with alcohol-related hepatitis admitted to a London teaching hospital from 2019 to 2021. Clinical and laboratory data was recorded from admission to discharge and/or death. Statistical analysis was undertaken using IBM SPSS v28.0. The prognostic utility of MDF, GAHS, MELD, ALBI, NLR and CLIF-C-AD scores in predicting 30-day mortality was determined by receiver operating curve analysis. Results: The cohort of 66 patients consisted of patients with a median age of 47, 58% were male, most had cirrhosis (pre-existing or subsequently proven), and most had sAAH with 74% recording an admission MDF >32 ( table 1 ). All patients had an NIAAA classification of definite or probable. One third required intensive care admission. Overall short-term mortality was poor (34% died at 30-days). When admission prognostic scores were compared to predict 30-day mortality, CLIF-C AD score performed best with an AUROC of 0.779 (CI 0.640–0.919, p <0.001) with the GAHS as second best with AUROC of 0.752. The difference between CLIF-C AD scores in patients with and without cirrhosis and alcohol-related hepatitis did not reach significance (p=0.07). The CLIF-C AD score retained best prognostic performance for 90-day mortality with c-statistic of 0.734 (p<0.001), marginally better that GAHS (0.730). Using the cut-offs for low (CLIF-C AD ≤ 45) and high risk (CLIF-C AD ≥ 60) for 90-day survival did not reach significance (Log rank test, p = 0.079). Conclusion: Admission CLIF-C AD score had the highest predictive performance of all the scores tested. This score may better identify those patients who would benefit greatest from aggressive early intervention and possible future pharmacological therapies. Further work is required, however CLIF-C AD shows potential as a good prognostic marker in sAAH. References: Sehrawat TS, Liu M, Shah VH. The knowns and unknowns of treatment for alcoholic hepatitis. Lancet Gastroenterol Hepatol. 2020 May;5 (5):494–506. doi: 10.1016/S2468-1253(19)30326-7 Liu M, Shah VH. New Prospects for Medical Management of Acute Alcoholic Hepatitis. Clin Liver Dis. 2019;13 (5):131–135. Baldin C, Piedade J, Guimarães L, Victor L, Duarte J, Veiga Z, Alcântara C, Fernandes F, Pereira JL, Pereira G. CLIF-C AD Score Predicts Development of Acute Decompensations and Survival in Hospitalized Cirrhotic Patients. Dig Dis Sci . 2021 Dec;66 (12):4525–4535. Johnson PJ, Berhane S, Kagebayashi C, et al . Assessment of liver function in patients with hepatocellular carcinoma: a new evidence-based approach-the ALBI grade. J Clin Oncol . 2015;33 (6):550–558. Ali S, Hussain S, Hair M, Shah AA. Comparison of Maddrey Discriminant Function, Child-Pugh Score and Glasgow Alcoholic Hepatitis Score in predicting 28-day mortality on admission in patients with acute hepatitis. Ir J Med Sci . 2013 Mar;182 (1):63–8. Singal AK, Louvet A, Shah VH, Kamath PS. Grand Rounds: Alcoholic Hepatitis. J Hepatol . 2018 Aug;69 (2):534–543.